The role of music therapy in palliative care - Stańczyk, Małgorzata Monika (Psychoonkologia, 2015)
This article relates to the use of music therapy in the palliative care. The first part of the article presents the role of music therapy in a holistic system of palliative care for oncology patients. The starting point was the definition of music therapy – applied by Susan Munro, the first time in relation to palliative care patients. According to Munro music therapy is a controlled and intentional use of the characteristics and potential of the music, which is a form of psychosocial and spiritual support, and improving the quality of life. Much space is devoted to music therapy forms and techniques that are applicable also in the palliative care. Music therapy programs implemented in foreign palliative care centers by B. Hogan and S. Weber. The second part of the article deals with the problem of quality of life. Questionnaires were analyzed in terms of quality of life research conducted in the use in palliative care. Much space is devoted to the issue of spirituality about in palliative care. Both, theoretical reflection on the quality of life as well as empirical reflection suggests that spiritual support is an important aspect of the quality of life for patients at the end of life.